Characterizing the KRAS G12C mutation in metastatic colorectal cancer: a population-based cohort and assessment of expression differences in The Cancer Genome Atlas. (May 2022) - Li, Meredith; Keshavarz-Rahaghi, Faeze; Ladua, Gale; Swanson, Lucas; Speers, Caroline; Renouf, Daniel J.; Lim, Howard J.; Davies, Janine M.; Gill, Sharlene; Stuart, Heather C.; Yip, Stephen; Loree, Jonathan M.
Introduction: In metastatic colorectal cancer (mCRC), RAS mutations impart inferior survival and resistance to anti-epidermal growth factor receptor (EGFR) antibodies. KRAS G12C inhibitors have been developed and we evaluated how KRAS G12C differs from other RAS mutations. Patients and Methods: This retrospective review evaluated patients in British Columbia, Canada with mCRC and RAS testing performed between 1 January 2016 and 31 December 2018. Sequencing information from The Cancer Genome Analysis (TCGA) was also obtained and analysed. Results: Age at diagnosis, sex, anatomic location and stage at diagnosis did not differ by RAS mutation type. Progression free survival on first chemotherapy for patients with metastatic KRAS G12C tumours was 11 months. Median overall survival did not differ by RAS mutation type but was worse for both KRAS G12C (27 months) and non-G12C alterations (29 months) than wildtype (43 months) ( p = 0.01). Within the TCGA, there was no differential gene expression between KRAS G12C and other RAS mutations. However, eight genes with copy number differences between the G12C and non-G12C RAS mutant groups were identified after adjusting for multiple comparisons ( FITM2, PDRG1, POFUT1, ERGIC3, EDEM2, PIGU, MANBAL and PXMP4) . We also noted that other RAS mutant mCRCs had a higher tumour mutation burden than those with KRAS G12C mutations (median 3.05 vs 2.06 muts/Mb, p = 4.2e–3) and that KRAS G12C/other RAS had differing consensus molecular subtype distribution from wildtype colorectal cancer (CRC) ( p < 0.0001) but not each other ( p = 0.14). Conclusion: KRAS G12C tumours have similar clinical presentation to other RAS mutant tumours, however, are associated with differential copy number alterations.